Copper-Powder-Catalyzed Synthesis of Pyrimidines from β-Bromo α,β-Unsaturated Ketones and Amidine Hydrochlorides - Jiao, Yang; Ho, Son Long; Cho, Chan Sik (Synlett, 2015)
β-Bromo α,β-unsaturated ketones are coupled and cyclized with amidine hydrochlorides in the presence of a catalytic amount of copper powder along with a base to give the corresponding pyrimidines in good yields.
Keywords: copper; coupling; cyclization; heterocycles; heterogeneous catalysis